Shear strength of reinforced concrete deep beams – A review with improved model by genetic algorithm and reliability analysis. (February 2020) - Shahnewaz, Md; Rteil, Ahmad; Alam, M. Shahria
Abstract: This paper reviews various models for the shear strength prediction of reinforced concrete (RC) deep beams with and without web reinforcement. A database of 381 tests on deep beams was utilized to conduct a comparative study among the analytical models and the code equations. The accuracy of each model was evaluated based on the statistical analysis and the performance test. It was found that code equations for the shear strength of RC deep beams are too conservative to estimate the shear strength of deep beams. Therefore, simplified improved shear equations for RC deep beams with and without web reinforcement were proposed from genetic algorithm (GA). The most significant parameters and their interactions that affect the shear strength of deep beams were identified by factorial design. The proposed equations were calibrated by reliability analysis which can be used for future design purposes. The resistance factors for the shear design equations were calculated at a target reliability index, βT of 3.5 in order to achieve an acceptable level of structural safety.